Influence of dairy housing on freshwater usage on commercial dairies in western Kansas - J.P. Potts; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2011)
Fresh water pumping records were obtained from 24 western Kansas dairy farms for a 10-year period from 2000 through 2009. Farms were divided by facility type: dry lot (DL), free stall (FS), or a combination (DL+FS). Of the facility types studied, DL averaged smaller (P<0.05) demand for water at 52.6 gal/cow per day compared with FS at 61.3 gal/cow. Both DL and FS facilities had less water demand than the combination facilities of DL+FS at 71.1 gal/cow of water daily. In all cases, average freshwater pumping was less than the daily amount of 134.7 gal/cow commonly used in dairy facility design. The difference may result from water conservation efforts of the dairies and the efficiency gained from operating larger milking parlors.; Dairy Day, 2011, Kansas State University, Manhattan, KS, 2011; Dairy Research, 2011 is known as Dairy Day, 2011
Keywords: Dairy Day; 2011; Kansas Agricultural Experiment Station contribution; no. 12-176-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1057; Dairy; Free stall; Dry lot; Water conversation